Sustainable Management of Energy, Storage, and Wireless Transfer in Electric Vehicles Operating in an Ecological Environment - Razek, Adel (Transportation Development Research, 2026)
Electric vehicles are progressively being employed for ecological transportation in green environments, thereby preserving eco-friendly biodiversity and ecosystems. The involved energy storage batteries are a crucial item of green mobility. The storage capacity state is intensely allied to the interconnection with energy supplies and charging methodologies, as well as the involved complexity. In an outstanding green urban background, charging schemes would operate wirelessly to transfer clean energy. However, the concerned wireless power transfer tools can implicate intricate settings and undesirable electromagnetic interferences. In this context, sustainable management of the condition of batteries and wireless chargers can improve their operation and reduce adverse effects. This includes the sustainable use of clean energy sources as well as the design and monitoring of complex interconnected systems. This contribution aims to highlight and analyse the role of a sustainable, clean, and efficient energy approach in the design and monitoring of energy storage and wireless transfer systems integrated into electric vehicles for environmentally friendly applications. The paper includes sections covering an introduction, electric mobility in a green urban context, energy storage and wireless power transfer, wireless electromagnetic interference and adverse effects, charging mode strategies, sustainable energy management in electric mobility, discussion, and conclusions. The research presented in this communication is based on a narrative review of the literature.